High Chloride Burden and Clinical Outcomes in Critically Ill Patients With Large Hemispheric Infarction - Gwak, Dong-Seok; Chung, Inyoung; Kim, Baik-Kyun; Lee, Sukyoon; Jeong, Han-Gil; Kim, Yong Soo; Chae, Heeyun; Park, Chan-Young; Han, Moon-Ku (Frontiers in Neurology, 2021)
Background: In general, disease severity has been found to be associated with abnormal chloride levels in critically ill patients, but hyperchloremia is associated with mixed results regarding patient-centered clinical outcomes. We aimed to investigate the impact of maximum serum chloride concentration on the clinical outcomes of critically ill patients with large hemispheric infarction (LHI). Methods: We conducted a retrospective observational cohort study using prospective institutional neurocritical care registry data from 2013 to 2018. Patients with LHIs involving over two-thirds of middle cerebral artery territory, with or without infarction of other vascular territories, and a baseline National Institutes of Health Stroke Scale score of ≥13 were assessed. Those with a baseline creatinine clearance of <15 mL/min and required neurocritical care for <72 h were excluded. Primary outcome was in-hospital mortality. Secondary outcomes included 3-month mortality and acute kidney injury (AKI) occurrence. Outcomes were compared to different maximum serum chloride levels (5 mmol/L increases) during the entire hospitalization period using multivariable logistic regression analyses. Results: Of 90 patients, 20 (22.2%) died in-hospital. Patients who died in-hospital had significantly higher maximum serum chloride levels than did those who survived up to hospital discharge (139.7 ± 8.1 vs. 119.1 ± 10.4 mmol/L; p < 0.001). After adjusting for age, sex, and Glasgow coma scale score, each 5-mmol/L increase in maximum serum chloride concentration was independently associated with an increased risk of in-hospital mortality (adjusted odds ratio (aOR), 4.34; 95% confidence interval [CI], 1.98–9.50; p < 0.001). Maximum serum chloride level was also an independent risk factor for 3-month mortality (aOR, 1.99 [per 5 mmol/L increase]; 95% CI, 1.42–2.79; p < 0.001) and AKI occurrence (aOR, 1.57 [per 5 mmol/L increase]; 95% CI, 1.18–2.08; p = 0.002). Conclusions: High maximum serum chloride concentrations were associated with poor clinical outcomes in critically ill patients with LHI. This study highlights the importance of monitoring serum chloride levels and avoiding hyperchloremia in this patient population.